Influence of Fe Buffer Layer on Co-Doped BaFe2As2 Superconducting Thin Films. (14th July 2015) - Bonavolontà, C.; de Lisio, C.; Valentino, M.; Laviano, F.; Pepe, G. P.; Kurth, F.; Iida, K.; Ichinose, A.; Tsukada, I.
Abstract : A systematic characterization of Co-doped BaFe2 As2 (Ba-122) thin films has been carried out. Two samples were available, one grown on CaF2 substrate and the other on MgO with an Fe buffer layer. The goal was to investigate films' magnetic and superconducting properties, their reciprocal interplay, and the role played by the Fe buffer layer in modifying them. Morphological characterization and Energy Dispersive X-ray analyses on the Fe-buffered sample demonstrate the presence of diffused Fe close to the Co-doped Ba-122 outer surface as well as irregular holes in the overlying superconducting film. These results account for hysteresis loops obtained with magneto-optic Kerr effect measurements and observed at both room and low temperatures. The magnetic pattern was visualized by magneto-optical imaging with an indicator film. Moreover, we investigated the onset of superconductivity through a measure of the superconducting energy gap. The latter is strictly related to the decay time of the excitation produced by an ultrashort laser pulse and has been determined in a pump-probe transient reflectivity experiment. A comparison of results relative to Co-doped Ba-122 thin films with and without Fe buffer layer is finally reported.